2019
DOI: 10.1111/acel.12915
|View full text |Cite
|
Sign up to set email alerts
|

Low plasma lysophosphatidylcholines are associated with impaired mitochondrial oxidative capacity in adults in the Baltimore Longitudinal Study of Aging

Abstract: The decrease in skeletal muscle mitochondrial oxidative capacity with age adversely affects muscle strength and physical performance. Factors that are associated with this decrease have not been well characterized. Low plasma lysophosphatidylcholines (LPC), a major class of systemic bioactive lipids, are predictive of aging phenotypes such as cognitive impairment and decline of gait speed in older adults. Therefore, we tested the hypothesis that low plasma LPC are associated with impaired skeletal muscle mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 35 publications
(42 reference statements)
0
29
0
Order By: Relevance
“…[37][38][39] Additionally, Semba et al have recently shown that low plasma LPC levels in humans, particularly LPC(16:1) and LPC(20:3), are associated with impaired mitochondrial oxidative capacity in skeletal muscle during ageing. 40 This dysregulation was also shown to be involved in muscle atrophy of tumour-bearing animals; however, this has yet to be confirmed in cancer patients. 41 In the present study, TAG species containing FA (18:3) and FA (20:5) in particular, were reduced in the plasma of cachectic cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] Additionally, Semba et al have recently shown that low plasma LPC levels in humans, particularly LPC(16:1) and LPC(20:3), are associated with impaired mitochondrial oxidative capacity in skeletal muscle during ageing. 40 This dysregulation was also shown to be involved in muscle atrophy of tumour-bearing animals; however, this has yet to be confirmed in cancer patients. 41 In the present study, TAG species containing FA (18:3) and FA (20:5) in particular, were reduced in the plasma of cachectic cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…The sets of features (variables) were imputed into four algorithms from the CARET package (v6.0-86), neural networks (NN) [ 124 , 125 , 126 ], Bayesian general linear model [ 127 ], C5.0 and RF [ 128 ]. In the feature selection step, RF is used to select features, whereas in the training step it is used as a classification algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…With regard to phospholipids, low plasma levels of lysophosphatidylcholines were found to be associated with impaired mitochondrial oxidative capacity in adults (Semba et al, ). Lower levels of blood phospholipids, including the lysophosphatidylcholine 18:2, were separately shown to be highly predictive of memory impairment in older adults (Mapstone et al, ).…”
Section: Lipid Biomarkers Of Aging In Humansmentioning
confidence: 99%